2001
DOI: 10.1016/s0735-1097(00)01139-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia impairs myocardial perfusion and permeability: role of oxidative stress and endogenous scavenging activity

Abstract: This study demonstrates that experimental HC is associated with blunted myocardial perfusion and increased vascular permeability responses in vivo to increased cardiac demand, which may be partly mediated by a shift in oxidative status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
99
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 44 publications
6
99
0
Order By: Relevance
“…Risk of CHD increases progressively with higher levels of low-density lipoprotein (LDL) cholesterol while higher levels of high-density lipoprotein (HDL) cholesterol reduces the risk significantly. Furthermore, CHD is also found to be associated with coronary endothelial dysfunction and myocardial perfusion abnormalities [15]. Several clinical trials have demonstrated that statin therapy is effective for both the primary and secondary prevention of coronary artery diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Risk of CHD increases progressively with higher levels of low-density lipoprotein (LDL) cholesterol while higher levels of high-density lipoprotein (HDL) cholesterol reduces the risk significantly. Furthermore, CHD is also found to be associated with coronary endothelial dysfunction and myocardial perfusion abnormalities [15]. Several clinical trials have demonstrated that statin therapy is effective for both the primary and secondary prevention of coronary artery diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of VEGF and VEGFR-2 in the vessel wall could account for the increased vascular permeability [23] and enhanced vasa vasorum neovascularization observed in experimental models of hypercholesterolemia [24]. Although the mechanism by which hypercholesterolemia may induce VEGF upregulation in the vessel wall remains unclear, possible pathophysiological stimuli include hypoxia [14], oxidative stress [3] and low NO bioavailability [4].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, VEGF upregulation has been proposed to be a non-specific stress-induced vascular response in the adult organism [25], or to constitute a vascular homeostatic mechanism for compensating endothelial dysfunction [1]. Independently of the mechanism responsible, sustained vascular VEGF overexpression could contribute to the atherosclerotic process by favoring lipoprotein infiltration through increased vascular permeability [23], inflammation [26] and angiogenesis [8]. The anti-atherosclerotic effect of the angiogenesis inhibitors endostatin and TNP-470 in the apoE−/− [10] would support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…This scanner has been proven to be an accurate (4), reproducible (25), and minimally invasive (27) tool for in vivo study of microcirculatory functional parameters, such as myocardial perfusion and permeability indices (27,29,30,32). The technical properties of the EBCT scanner (model C-150; Imatron, South San Francisco, CA) have been described in detail elsewhere (27,32,33). Animals were positioned supine in the EBCT gantry so that the heart was centered in the imaging field and fixed in the position for the subsequent studies.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been shown that myocardial microvascular permeability can change under various pathologic and metabolic circumstances such as diabetes mellitus (24,41), hypercholesterolemia (32), hypertension (31), and acute myocardial ischemia followed by reperfusion (29). Embolization of microscopic plaque debris into the distal coronary bed during coronary interventions is a common and frequent event (9,10,35) that might be associated with microinfarctions and with adverse clinical outcome (7,10).…”
mentioning
confidence: 99%